COMPARISON OF RECENTLY USED PHACOEMULSIFICATION SYSTEMS USING A HEALTH TECHNOLOGY ASSESSMENT METHOD. (6th July 2017) - Huang, Jiannan; Wang, Qi; Zhao, Caimin; Ying, Xiaohua; Zou, Haidong
Abstract : Objectives: To compare the recently used phacoemulsification systems using a health technology assessment (HTA) model. Methods: A self-administered questionnaire, which included questions to gauge on the opinions of the recently used phacoemulsification systems, was distributed to the chief cataract surgeons in the departments of ophthalmology of eighteen tertiary hospitals in Shanghai, China. A series of senile cataract patients undergoing phacoemulsification surgery were enrolled in the study. The surgical results and the average costs related to their surgeries were all recorded and compared for the recently used phacoemulsification systems. Results: The four phacoemulsification systems currently used in Shanghai are the Infiniti Vision, Centurion Vision, WhiteStar Signature, and Stellaris Vision Enhancement systems. All of the doctors confirmed that the systems they used would help cataract patients recover vision. A total of 150 cataract patients who underwent phacoemulsification surgery were enrolled in the present study. A significant difference was found among the four groups in cumulative dissipated energy, with the lowest value found in the Centurion group. No serious complications were observed and a positive trend in visual acuity was found in all four groups after cataract surgery. The highest total cost of surgery was associated with procedures conducted using the Centurion Vision system, and significant differences between systems were mainly because of the cost of the consumables used in the different surgeries. Conclusions: This HTA comparison of four recently used phacoemulsification systems found that each of system offers a satisfactory vision recovery outcome, but differs in surgical efficacy and costs.